Absolute reliability and validity of the OptoGaitTM system to measure spatiotemporal gait parameters during running - Garcia-Pinillos, F.; Latorre-Román, P. A.; Chicano-Gutiérrez, J. M.; Ruiz-Malagón, E. J.; Párraga-Montilla, J. A.; Roche-Seruendo, L. E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
The biomechanics of walking and running, in both ground and treadmill conditions, have been extensively analysed and important differences have been reported. Despite some previous studies having examined the validity and reliability of the OptoGait™ system for measuring gait characteristics during walking, no previous works have determined the reliability and validity of this system while running on a treadmill. Therefore, this study aimed to determine the absolute reliability (within-subject variation) and evaluate the concurrent validity of the OptoGait™ system for measuring spatiotemporal variables while running at a comfortable speed by comparing data with a highly accurate system of measuring those parameters (i.e. video analysis at 1000 Hz). Forty-nine endurance runners performed a running protocol on a treadmill at a comfortable speed. Two systems were used to collect data: OptoGait™ system and high-speed video analysis at 1000 Hz. The coefficient of variation (CV) was calculated as a measure of absolute reliability. The OptoGait™ system reported a CV range between 2.2% and 11.4% for spatiotemporal parameters, while the video analysis showed a CV range between 0.02% and 9.9%. To determine concurrent validity, intra class correlation coefficients (ICC) and pairwise comparisons of means (t-test) were calculated between data from both systems. Although the paired t-test demonstrated significant differences between systems, a high level of agreement (ICC > 0.89) was obtained in spatiotemporal parameters between systems. When compared to a high-speed video analysis at 1000 Hz, the results indicate that the OptoGait™ system is a reliable and valid tool to measure spatiotemporal gait characteristics while running on a treadmill at a comfortable speed.